Evaluation of physical and sensory quality attributes of three mango varieties at three stages of ripeness, grown in lower eastern province of Kenya - part 1 - Okoth, E.M.; Sila, D.N.; Onyango, C. A.; Owino, W.O.; Musembi, S.M.; Mathooko, Francis M. (My University, 2014)
Physical attributes at three stages of ripeness (unripe, intermediate and fully ripe) and sensory quality at full ripe stage of Apple, Ngowe and Kent mango varieties grown in Lower Eastern Province (Machakos and Kitui) of Kenya were evaluated. They were stored under ambient temperatures of 25ºC and relative humidity of 65-70. Apple and Ngowe ripened fully after 7 days whereas Kent took 10 days. The weight and firmness decreased with increasing ripeness and was accompanied by notable colour change for all the varieties. Kent had the most firm skin (5.8KN) and flesh (3.7KN) whereas the softest was Apple with a skin and flesh firmness of 0.6KN and 0.07KN respectively. There were clear differences in skin and flesh color in different varieties (p≤0.05). At the unripe stage, Ngowe exhibited the greenest colour on the skin, however with increasing ripeness, the skin and flesh colors turned from green to yellow/orange; the most yellow variety being Kent. The heaviest variety was Ngowe (>625g) at unripe stage, while Apple had the lowest w eight (363.46g) at the ripe stage. All the varieties lost weight with increasing ripeness, with Kent varieties exhibiting the most remarkable total mean weight loss (>15g). The highest and lowest varieties in pulp yield were Apple (75%) and Ngowe (70%) respectively. The most and least preferred skin fruit colour Kent and Ngowe varieties with a mean score of 6.54±1.5 and 5.61±1.7 respectively. The most preferred flesh colour, flavor, taste, texture and overall acceptability was the Apple varieties, followed by the Ngowe and lastly Kent variety. This clearly showed that different varieties have different physical and sensory characteristics where Apple varieties would be most suitable for fresh consumption and in processing due to it higher yields than the rest. This study revealed that variety and stage of ripeness had influence on physical and sensory attributes of the varieties analyzed.